The five stable noble gases are sensitive unambiguous tracers of glacial meltwater. Issue 8 (16th April 2014) - Loose, B.; Jenkins, W. J.
Abstract The five inert noble gases—He, Ne, Ar, Kr, and Xe—exhibit a unique dissolved gas saturation pattern resulting from the formation and addition of glacial meltwater to seawater. He and Ne become oversaturated, and Ar, Kr, and Xe become undersaturated to varying percentages. For example, addition of 10‰ glacial meltwater to seawater results in a saturation anomaly of ΔHe = 12.8%, ΔNe = 8.9%, ΔAr = −0.5%, ΔKr = −2.2%, and ΔXe = −3.3%. This pattern in noble gas saturation reflects a unique meltwater signature that is distinct from the other major physical processes that modify the gas concentration and saturation, namely, seasonal changes in temperature at the ocean surface and bubble mediated gas exchange. We use Optimum Multiparameter analysis to illustrate how all five noble gases can help distinguish glacial meltwater from wind‐driven bubble injection, making them a potentially valuable suite of tracers for glacial melt and its concentration in the deep waters of the world ocean.